'This isn't a movie . . . it's a tourism ad for Australia': The Dundee campaign and the semiotics of audiovisual tourism promotion. (June 2020) - Leotta, Alfio
This article proposes a theorization of audiovisual media promotion as a distinct media field. Despite their omnipresence, very few scholars have examined the aesthetic, thematic and institutional characteristics of tourism films, commercials and promotional videos. The field of tourism audiovisual promotion poses a significant conceptual challenge as it consists of a vast array of diverse media texts and aesthetic forms. Such vast aesthetic differences, along with the different promotional potential associated with each of these forms, complicate any straightforward definition of this media field. This article will use the analysis of a recent case study – the Dundee campaign launched by Tourism Australia in 2018 – to develop a theorization of audiovisual tourism promotion. In particular, it will argue that the meaning and function of tourism audiovisual promotional texts are determined by a 'discursive framework' which, in turn, is informed by converging textual and contextual factors.